Criterion Validity of the activPAL Activity Monitor for Sedentary and Physical Activity Patterns in People Who Have Rheumatoid Arthritis. Issue 7 (1st July 2016) - Larkin, Louise; Nordgren, Birgitta; Purtill, Helen; Brand, Charles; Fraser, Alexander; Kennedy, Norelee
Abstract: Background: Accurate measurement of physical activity and sedentary behavior is an important consideration for health care professionals. The activ PAL activity monitor has not been validated against a criterion measure for people with rheumatoid arthritis (RA). Objective: The objective of this study was to determine the criterion validity of the activ PAL activity monitor for measuring step counts, transition counts, and time spent in sedentary, standing, and walking behaviors in people with RA. Design: A laboratory-based criterion validation study was conducted. Methods: Participants with a confirmed medical diagnosis of RA were recruited from 2 outpatient rheumatology clinics. The testing procedure consisted of standardized testing components and tasks related to activities of daily living. Participants wore an activ PAL activity monitor and were video recorded throughout the testing procedure. Direct observation was used as the criterion measure. Data analysis consisted of validation analysis of the activ PAL activity monitor data and the criterion measure data. Results: Twenty-four people participated in the study. Data from 20 participants were included in the final analysis. The activ PAL significantly underestimated step counts by 26% and transition counts by 36%. There was no significant difference between the activ PAL activity monitor and the criterion measure for time spent in sedentary, standing or light activity, and walking behaviors. Limitations: Validation of activities of daily living in a laboratory environment is a limitation of this study. Conclusions: The activ PAL activity monitor underestimated step and transition counts and, therefore, is not valid for measuring these outcomes in people with RA. Relative to direct observation, the activ PAL activity monitor is valid for measuring time spent in sedentary, standing, and walking behaviors in people with RA.